A mixed methods systematic review of multimodal non-pharmacological interventions to improve cognition for people with dementia. (May 2020) - Chalfont, Garuth; Milligan, Christine; Simpson, Jane
Objective: Multimodal non-pharmacological interventions have been argued to have the potential to complement current pharmacological approaches to improving quality of life for people living with dementia. The aim of this review was to identify, synthesise and appraise the evidence for the effectiveness of multimodal non-pharmacological interventions for improving cognitive function specifically. Method: After a comprehensive search strategy including grey literature, 26 studies were reviewed. The inclusion criteria concerned adults with a primary diagnosis of dementia. Studies used two or more different modes of intervention, and measured a cognitive outcome. Due to differences in the conceptualisations of the term 'multimodal', a typology of modes and methods was developed to facilitate classification of candidate studies. Results: Twenty-one group studies and five case studies were found. Group studies used two or three modes of intervention and multiple methods to implement them. Interventions utilised were cognitive, physical, psychological and psychosocial, nutrition, fasting, gut health, sleep hygiene, stress reduction, detoxification, hormonal health and oxygen therapy. Five individual case studies were found in two separate papers. Each personalised patient treatment utilised in-depth assessments and prescribed up to nine different modes. In 19 (90%) of the 21 group comparisons, participants were reported to have cognitive improvements, stability with their dementia or a delay in their decline. The extent of these improvements in terms of meaningful clinical change was variable. Conclusion: Multimodal non-pharmacological interventions have the potential to complement singular therapeutic approaches by addressing multiple modifiable risk factors currently understood to contribute towards cognitive decline.